Effect of Maximum Voltage Angle on Three-Level Single Phase Transformerless Photovoltaic Inverter Performance - M. Irwanto; M.R. Mamat; N. Gomesh; Y.M. Irwan (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
This paper presented a new topology of three-level single phase transformerless photovoltaic inverter (TPVI). It consisted of three main circuits; they were a pulse driver circuit, a full bridge inverter circuit and a power factor correction (PFC) circuit that had functions as production of pulse waves, to develop alternating current (AC) waveform and to stabilize voltage of photovoltaic (PV) array, respectively.  In this research, AC three-level waveform single phase TPVI was developed and created by a microcontroller PIC16F627A-I/P with varied maximum voltage angle from 200 to 1800 and observed on 28th February 2014 between  9.00  am to 17.00 pm, and also analyzed effect of maximum voltage angle on the three-level single phase TPVI performance.  The result showed that maximum voltage angles of the TPVI effected on root mean square value of AC voltage, current and power. If the maximum voltage angle was increased, therefore value of the AC voltage, current and power would increase. The maximum voltage angle would effect on the current total harmonic distortion (CTHD), the lowest CTHD of 15.448% was obtained when the maximum voltage angle was 1340